2020
DOI: 10.3389/fonc.2020.00353
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Prediction of Microvascular Invasion in Hepatocellular Carcinoma: Initial Application of a Radiomic Algorithm Based on Grayscale Ultrasound Images

Abstract: Objectives: To establish a radiomic algorithm based on grayscale ultrasound images and to make preoperative predictions of microvascular invasion (MVI) in hepatocellular carcinoma (HCC) patients. Methods: In this retrospective study, 322 cases of histopathologically confirmed HCC lesions were included. The classifications based on preoperative grayscale ultrasound images were performed in two stages: (1) classifier #1, MVI-negative and MVI-positive cases; (2) classifier #2, MVI-positive cases were further clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…Xu et al ( 15 ) recently assessed the radiomics characteristics for MVI prediction, and demonstrated that the radiomics signatures of contrast-enhanced CT were less important than the radiological features, with the AUC value from 0.787 to 0.841. In addition, the radiomics nomogram has also been used in the ultrasound images for MVI prediction with the reported AUC value of 0.731 ( 16 ) and 0.806 ( 17 ), respectively. Comparatively, our proposed deep learning framework with 3D CNN yielded the performance with the AUC value of 0.926, which is better than the reported radiomics approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al ( 15 ) recently assessed the radiomics characteristics for MVI prediction, and demonstrated that the radiomics signatures of contrast-enhanced CT were less important than the radiological features, with the AUC value from 0.787 to 0.841. In addition, the radiomics nomogram has also been used in the ultrasound images for MVI prediction with the reported AUC value of 0.731 ( 16 ) and 0.806 ( 17 ), respectively. Comparatively, our proposed deep learning framework with 3D CNN yielded the performance with the AUC value of 0.926, which is better than the reported radiomics approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al ( 15 ) recently analyzed the contrast-enhanced CT based on radiomics analysis to predict MVI and outcome in HCC, and demonstrated that the combination of radiological and imaging radiomics features could produce better performance in predicting MVI. In addition, there also have been some reports about radiomics predicting MVI based on ultrasound images ( 16 , 17 ). As pointed out by the recent study ( 8 ), researchers currently construct radiomics models based on single modality image data, and the use of multimodality for MVI prediction has not to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…For the former, although the sample size was small (47 patients with HCC), a radiomics-based study including B-mode, share wave elastography (SWE) and viscosity imaging demonstrated high diagnostic ability (AUC 0.94) to predict Ki-67, which is a marker to indicate the poor prognosis of several malignant diseases [ 48 ]. For the latter, two retrospective studies using B-mode US findings showed AUCs of 0.731 and 0.726 (0.806 for differentiation between M1 and M2) in predicting MVI [ 49 , 80 ]. In addition, Yao et al reported a higher diagnostic ability (AUC 0.98) achieved by radiomics-based multimodal US images [ 48 ].…”
Section: Radiomics-based Us For the Diagnosis Of Hccmentioning
confidence: 99%
“…However, these techniques involve radiological exposure, and are laborious to perform and costly. Recently, Dong et al[ 30 ] published a study using radiomic algorithms based on grayscale ultrasound images to elaborate radiomic signatures with the potential to aid in the prediction of VMI, with promising results. Ji et al[ 31 ] created predictive models for recurrence after surgical resection using radiomic techniques to analyze contrast-enhanced CT images, with a C-index of 0.633-0.699.…”
Section: Ai In the Treatment Of Hccmentioning
confidence: 99%